Equipment Parameter Investigation for a Proposed Power Conductor Hot Spot Identification system - Polycarpou, Alexis; Komodromos, Michael; Kalli, Kyriacos; Argyrou, Maria C.; Ioannou, Andreas (My University, 2023)
Reliability, efficiency and continuity of power energy supplied is an area which receives increasing attention as the main infrastructure of power transmission and distribution systems in many countries is ageing. Hot spot related cable failures and power interruptions have a big financial impact on the power provider. The operational parameters of a method to identify in real time hot spots on cables is investigated in this paper, which can result to timely fault prevention. This can be achieved through exploiting the optical sensing capabilities of the existing optical fibre on-grid network. The resulting parameters aim to be advantageous for the system as they increase accuracy and will enable the Remote, automated, continuous, and real time monitoring of the grid infrastructure integrity.
Keywords: cable remote monitoring; hot spots; Optical fiber